Housing and Socio-Spatial Inclusion - Rogers, Dallas (2015)
This special issue on housing and socio-spatial inclusion had its genesis in the 5th Housing Theory Symposium (HTS) on the theme of housing and space, held in Brisbane, Australia in 2013. In late 2013 we put out a call for papers in an attempt to collect an initial suite of theoretical and empirical scholarship on this theme. This collection of articles progresses our initial discussions about the theoretical implications of adding the “social” to the conceptual project of thinking through housing and space. We hope that this special issue will act as a springboard for a critical review of housing theory, which could locate housing at the centre of a much broader network of social and cultural practices across different temporal trajectories and spatial scales. This editorial presents an overview of the theoretical discussions at the HTS and summarises the six articles in this themed issue, which are: (1) The meaning of home in home birth experiences; (2) Reconceptualizing the “publicness” of public housing; (3) The provision of visitable housing in Australia; (4) The self-production of dwellings made by the Brazilian new middle class; (5) Innovative housing models and the struggle against social exclusion in cities; and (6) A theoretical and an empirical analysis of “poverty suburbanization”.